2002
DOI: 10.1093/annonc/mdf289
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of second malignancy after treatment of Hodgkin’s disease: the influence of treatment, age andfollow-up time

Abstract: In a long-term follow-up study of HD patients of all ages, the SIR of solid tumors was high in patients treated at young age and decreased with increasing age. Most solid tumors had started within or at the edge of the irradiated field, and SIR of solid tumors increased even 20-30 years after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 21 publications
4
62
1
3
Order By: Relevance
“…4,7,[11][12][13][14] A protective effect of breastfeeding on the risk of premenopausal breast cancer has been observed in several studies, although not in all analyses. [31][32][33][34][35][36][37] Although the small size of this cohort prohibits analysis of the possibility that lactation might be protective, further studies in larger survivor cohorts may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,[11][12][13][14] A protective effect of breastfeeding on the risk of premenopausal breast cancer has been observed in several studies, although not in all analyses. [31][32][33][34][35][36][37] Although the small size of this cohort prohibits analysis of the possibility that lactation might be protective, further studies in larger survivor cohorts may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the latter observation is unclear. Although rituximab has been associated with increased long-term risk of solid malignancies in patients with lymphoma (32), this association has not been shown in the rheumatoid arthritis population (26,33). Patients should be educated about these risks when choosing between treatment regimens.…”
Section: Malignanciesmentioning
confidence: 99%
“…Radiation therapy also has been associated with increased melanoma development, as seen in a study of patients with Hodgkin lymphoma. 88 In this cohort, the incidence ratio of both melanoma and NHL increased significantly and melanoma risk remained increased for more than 20 years, with most tumors forming within or at the boundaries of the irradiated field. Similar observations have been made in the breast cancer literature, with studies noting increased risk of melanoma in patients with breast cancer and in those treated with irradiation.…”
Section: Clinical Course Of Melanoma In Lymphoma Patientsmentioning
confidence: 68%